Identificação da lesão e avaliação da presença de atividade da neovascularização da coroide secundário à degeneração macular relacionada à idade com o exame de Octa versus métodos tradicionais de Retinografia, Angiografia e SD-OCT - Santos, Daniela Calucci Dos [UNIFESP] (2020)
Objective: To identify parameters of the retinal and choroidal vascular structure of the OCTA method that identify MNV activity and that can be used as markers of MNV activity. Methods: A retrospective study that included 23 eyes of 23 patients aged 50 years with exudative AMD who underwent anti-angiogenic therapy between 2015 and 2017 and evaluated two consecutive visits with an interval equal to or greater than three months. All images were qualitatively evaluated by a masked examiner. The criteria adopted for the analysis of the presence of NVM activity in the traditional diagnostic tests were: presence of hemorrhage, exudation and / or retinal edema for color retinography, late leakage for angiofluoresceinography, plaque and / or hot spot in green indocyanine angiography, fluids. OCT and dense vascular network composed of thin capillary numbers, peripheral arch containing anastomotic terminal vessels and perilesional hypointense halo in OCTA. Statistical analysis was performed using the observed coefficient of agreement and the p coefficient to verify the association between the studied variables and Fisher's exact test to assess independence between OCTA findings and diagnostic tests. The level of statistical significance adopted was p <0.05. Results: In this study, considering the existence of at least one of the vascular architecture criteria analyzed in OCTA as a sign of NVM activity, it was concluded that there is no relationship of dependence or association between the vascular characteristics found in OCTA and the classic signs of NVM activity in the AGF and SD-OCT gold standard examinations. Conclusions: Although the isolated analysis of the vascular criteria chosen in OCTA had no impact on the association with the identification of NVM activity with the gold standard exams, it was possible to observe that there are structural changes in the blood vessels that compose NVM such as large vessels persistent treatment with anti-VEGF, thin capillaries and anastomotic vessels undergoing vascular transformation in the NVM activation and reactivation cycles due to the different levels of VEGF present. Then it is possible to think of OCTA as a promising method to show the benefit of vascular nonproliferation.